1984
DOI: 10.1088/0029-5515/24/1/006
|View full text |Cite
|
Sign up to set email alerts
|

The structure of magnetic fluctuations in the HBTX-1A reversed field pinch

Abstract: Arrays of edge magnetic coils and statistical analysis techniques have been used to investigate the magnetic fluctuation structure in the HBTX-1A reversed field pinch. The superficially random fluctuations can in fact be attributed almost entirely to global modes with poloidal mode number m = 0 and 1, provided account is taken of toroidal distortion of the modes. A toroidal array of coils discloses a broad spectrum of toroidal mode numbers with peak at Inl ~ 10 and significant variation with time and frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(46 citation statements)
references
References 10 publications
9
37
0
Order By: Relevance
“…Most of the observed m ϭ2 fluctuation presumably results from toroidal distortion of the mϭ1, as first reported for the High Beta Toroidal Experiment ͑HBTX-1A͒ RFP. 9 The close correspondence in frequency which can be seen in Fig. 10 suggests that the independent mϭ2 fluctuations are small in MST.…”
Section: Results Of Experimentsmentioning
confidence: 61%
“…Most of the observed m ϭ2 fluctuation presumably results from toroidal distortion of the mϭ1, as first reported for the High Beta Toroidal Experiment ͑HBTX-1A͒ RFP. 9 The close correspondence in frequency which can be seen in Fig. 10 suggests that the independent mϭ2 fluctuations are small in MST.…”
Section: Results Of Experimentsmentioning
confidence: 61%
“…Magnetic fluctuations play a substantial role in the global dynamics of the RFP and much work has been carried out previously to characterize magnetic tearing mode behavior in the RFP. 5,[27][28][29][30][31][32][33] Direct measurements of the tearing mode spectrum in the core of MST are not available for any quantity, including magnetic fields. Nevertheless, magnetic mode spectral mea- surements are routinely made at the plasma wall by arrays of magnetic coils.…”
Section: B Extracting Tearing Mode Flowsmentioning
confidence: 99%
“…29 The observations of discrete relaxation in the RFP plasmas showed that the relaxation may go on in an oscillatory manner. The loop voltage, reversal parameter, and electron current all have sawtooth character [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] during the relaxation. The loop voltage and fluctuation amplitudes peak at the sawtooth crash.…”
Section: Jϭ"؋bϭb ͑1͒mentioning
confidence: 99%
“…63. Since the MHD dynamo action was introduced into the RFP plasma, 55 the MHD dynamo theory has enjoyed considerable success in the physics of the laboratory plasma and is well supported by the experimental phenomenology [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and the numerical simulations. 66 -77 It is of great importance to the physics of the RFP plasma that the MHD dynamo electric field and mean-field Ohm's law have been verified in the recent experiment.…”
Section: Jϭ"؋bϭb ͑1͒mentioning
confidence: 99%
See 1 more Smart Citation